(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
Population growth is one of the most significant factors influencing environmental change in the modern world. As the number of people increases, the demand for natural resources, energy, and land also rises, leading to environmental degradation. This article examines the relationship between population growth and environmental issues, highlighting key challenges and possible solutions.